Nutritional characteristics and phytochemical screening of traditional panai (Borassus flabellifer) olai kozhukattai (Journal of Food and Dietetics Research, 2021)
Objectives: Panai Olai Kozhukattai (POK) or simply palm leaf dumpling is a traditional south Indian delicacy  which is very much popular in Tamil Nadu, India. POK preparation by traditional methods involves mixing all the  ingredients to form a thick paste, which is then wrapped in tender palm leaf strips and cooked using steam under  pressure. The present paper is the first-ever attempt on studying the nutritional characteristics of POK.  Material and Methods: The nutritional analysis of POK involves proximate analysis, and vitamin and mineral  composition.  Results: The proximate analysis results demonstrated that POK is nutritionally predominant over the other South  Indian breakfast foods. High levels of fat-soluble vitamins were present in POK. Water-soluble vitamins including  niacin, pyridoxine, thiamine, and riboflavin were found in POK and with a high percentage of riboflavin. Among  the mineral elements analyzed, the concentration of potassium in POK sample was the highest followed by  magnesium, phosphorous, manganese, zinc, iron, and selenium. The study also documented a protocol of POK  preparation. It is believed that the steaming in the palm leaves gives the palm leaf flavor to POK and it also  transfers phytonutrients into the product from the palm leaves. Hence, the paper also focuses on investigating  the presence of essential bioactive compounds in POK using qualitative phytochemical tests. The phytochemical  screening of methanol extracts of POK revealed the presence of certain phytochemicals such as flavonoids,  alkaloids, glycosides, and saponins and total flavonoid content of POK was estimated to be 148.25 mg/100 g.  Conclusion: Overall, the study leads to the documentation of a preparation protocol along with the nutritional and  phytochemical aspects of traditional POK with a view to promoting its consumption in other parts of the world.
Keywords: Palm jaggery; Palm leaves; Panai Olai Kozhukattai (POK); Phytochemicals; Borassus flabellifer